THE URGENCY OF UNDERSTANDING ISLAMIC HISTORY ACCORDING TO YUSUF QARADAWI'S PARADIGM - Abdullah Ghulam Nazih; Evalinda Evalinda; Ali An Sun Geun (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
Secularists often spread lies about Islamic history and thus distort Islamic history. As Muslims, we must maintain the authenticity of Islamic history so that it can be properly understood by current and future generations. This article discusses the urgency of understanding Islamic history theoretically, as well as according to the paradigm of Yusuf Al Qardhawi which will be described in detail in this article. By using a descriptive qualitative approach with the aim of defining history, historical urgency, as well as describing theory and development, interpreting Yusuf Al Qaradawi's paradigm of the urgency of understanding Islamic history. This study resulted in the following discussions: 1) Yusuf Musthafa al-Qardhawi is one of the great scholars born in Cairo as well as a Muslim scholar who has had many works in various fields of science; 2) history is the knowledge or science of important events and events for many people or societies that occurred in the past that occurred to humans, society and nature chronologically or not; 3) History has 3 important essences, namely history as a science, history as events and history as stories; 4) By studying Islamic history, it is hoped that one can know and understand the growth and development of Islamic civilization, from the time of its birth to the present, and 5) According to Yusuf Al Qardhawi, the de-Islamization movement that aims to decredit Islam one of them is historical distortion, not all information recorded in history books is one hundred percent true. Many history books have distorted and lies that can be proven through intensive study. Therefore, it is important to study Islamic history that is studied by Muslims themselves so that Islamic history does not occur distortions).